Some areas of modernization of technical education: on the material of scientific and methodological research conducted at the Kharkiv National University of Civil Engineering and Architecture - Cherednik, D.; Dansheva, S. (New Collegium, 2020)
The article deals with the renovation of the educational process in high technical school. The analysis of normative and legal acts regulating the future specialists training quality in higher school is made. The main professionally significant qualities and abilities required by a future technical specialist in a competitive environment are described. A system of measures is presented that will allow preparing specialists who: strive to increase the level of their professional qualities; able to quickly and clearly navigate in difficult situations; able to think creatively; able to solve many problems of a professional nature. To introduce author’s point of view on the need to create innovative conditions for the training of future technical specialists at the university is presented. Features of teaching physics in the process of education program realization are considered, taking into account competency approach in education. The article presents the meaning: modernization of the educational and material base; development of new educational standards and curricula; updating the content of education; fundamentalization and professionalization of the educational process; development of innovative learning technologies. The article meets the modern requirements for the reform of higher technical education in general. It is of interest to the administrative board of universities, teachers, researchers, graduate students, future bachelors and masters. Features of teaching physics in the process of education program realization are considered, taking into account competency approach in education and peculiarities of competency formation in the process of studying physics in overall structure of competencies, according to Federal State Educational Standards in Agricultural Engineering The research presented in the article can be used to conduct scientific-pedagogical and scientific-methodical seminars, round tables and scientific conferences in higher education institutions.